Study efforts, learning strategies and test anxiety when striving for language competence: the role of utility value, self-efficacy, and reasons for learning English - Üner, Ayça; Mouratidis, Athanasios; Kalender, İlker (Educational Psychology, 2020)
Previous research has shown that utility value and expectancy forsuccess, as well as the reasons for academic striving, could partlyexplain academic engagement. Yet, their joint role in predictinglearning strategies and test anxiety has not been thoroughlyunderstood, especially in contexts where pressure for success ishigh. We examined this issue in a sample of Turkish universitystudents who were attending a language preparatory school(N¼1009; 53% males,Mage¼19.14years;SD¼1.08) and wereunder the psychological pressure to pass their qualifying exams.Regression analyses showed that next to self-efficacy beliefs, itwas intrinsic reasons which positively and consistently predictedlearning strategies; in contrast, self-worth concerns positively pre-dicted test anxiety. These relations emerged even among stu-dents who experienced failure and were thus psychologicallypressed to succeed. Our findings suggest that intrinsic reasons foracademic striving might play a decisive role even in psychologic-ally pressuring contexts